Analisis Sensitivitas Salinitas dan Adsorbsi Injeksi Surfaktan-Polimer Menggunakan Simulasi Reservoir Pada Reservoir Berlapis Lapangan NA - Rita, Novia (UIR PRESS, 2016)
Increasing the time, the condition of the oil in reservoir increasingly difficult for production to the surface, this is caused by diminishing reservoir pressure and the condition of a viscous oil. While the technology used can no longer urged oil to surface. NA field is a field that is old, the production process is done on the field NA has been through the stages of primary and secondary recovery, where this stage is not optimal in increasing oil production on the field. While OOIP on the field is still economically viable. Of screening criteria that has been done on NA Field, the oil production stage to do next is to EOR method. The EOR methods that can be applied is by chemical injection method of surfactant and polymer. Before the surfactant and polymer injection method performed on NA Field, the first done through the stages of planning reinjection reservoir simulation. Fields of reservoir simulation models NA will be analyzed four skenarios conducted for sensitivity to salinity and adsorption of surfactant-polymer. Skenario 1 simulation with values ââvarying salinity, Skenario 2 adsorption value simulation with different surfactants, Skenario 3 sensitivity to polymer adsorption, Skenario 4 see changes impairment influences the permeability to polymer injection. The results of all four skenarios simulations obtained optimum value of cumulative production of 72 548 STB with a recovery factor (RF) of 30.9% at the price of 0.075 surfactant salinity mEq / ml, adsorption of surfactant 0.3 mEq / ml, 0.1 wt polymer adsorption % cuft, and changes in permeability due to 80wt% polymer solution cuft.